KOMPATIBILITAS DEMOKRASI DAN ISLAM DALAM PERSPEKTIF KHALED ABOU EL-FADL - Faiz, Fahruddin (Jurnal Review Politik, 2013)
Democracy and capitalism is regarded as the final system of economic and political systems. All people don’t accept the democracy as the best final political system, including among Muslims. This study intends to look at the compatibility of democracy and Islam by Khaled Abou El Fadl’s view. This library research found that according to El Fadl, a consistent practice of Islam should be brought to the practice of democratic politics, any institutional system that is used. The basic values of democracy, namely respect for difference, actually contained in the Qur'an, and even the early generations of Islam had been implemented well. El Fadl positive perspective towards democracy can not be separated from the development paradigm of anti-authoritarianism